Developing a novel approach for improving supply chain management for SARS-CoV-2 point-of-care diagnostic services in resource-limited settings : a case study of Mopani district Municipality in Limpopo Province, South Africa - Mashamba‑Thompson, Tivani Phosa (University of Pretoria, 2023)
Thesis (PhD (Public Health))--University of Pretoria, 2023.